شعرية توظيف الشخصية في رواية مملكة الموز - يسقط الملك - لبوعلام بطاطاش - مرغني, سمية (جامعة الوادي - University of Eloued, 2021)
الملخص أثارت الشخصية اهتمام النقاد والدارسين عبر العصور، لما لها من أهمية بالغة ومكانة مهمة فهي بمثابة المحور التي تجمع كل العناصر السردية وبناء على ذلك فإن هذه الدراسة جاءت لتكشف عن شعرية توظيف الشخصية في رواية " مملكة الموز" – يسقط الملك- للكاتب الجزائري بوعلام بطاطاش ، عبر تناول تصنيفها في النص السردي وبنيتها العاملية، إضافة إلى المربع السيميائي. The character has aroused the interest of critics and scholars through the ages, because of its great importance and important position, as it is the axis that brings together all the narrative elements. Accordingly, this study came to reveal the poetic employment of the character in the novel "The Banana Kingdom" - The King Falls - by the Algerian writer Boualem Batatash, by addressing its classification in the narrative text and its global structure, in addition to the semiotic square.
The Poetic Employment Of The Character In The Novel The Banana Kingdom - The Fall Of The King - By Boualem Batatash
مقال
Keywords: الشعرية- الشخصية- تصنيف الشخصية – النموذج العاملي – المربع السيميائي; poetic - personality – character classification – factorial model - semiotic square.